FRAGSTATS: A Free Tool for Quantifying and Evaluating Spatial Patterns - Benxin Chen; Basil V. Iannone III (EDIS)
Human activities such as urbanization and agriculture have triggered rapid land cover change, resulting in the loss of natural ecosystems. Land managers managers seeking to plan effectively for future land use that preserves biodiversity and the valuable services provided by natural ecosystems must understand land cover change and its environmental impacts. Quantifying patterns of land cover change objectively in order to understand them can be difficult without the proper resources, however. This 9-page fact sheet written by Benxin Chen and Basil V. Iannone III and published by the UF/IFAS School of Forest Resources and Conservation introduces one such resource, a free software called FRAGSTATS. Readers will learn to create input data, run the FRAGSTATS software, and interpret outputs. A few basic concepts of landscape ecology and GIS are included, but this fact sheet is intended for readers with at least some GIS knowledge.